2018
DOI: 10.1007/s11205-018-1875-6
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Study on the Antecedents of Work–Life Balance from the Fit and Balance Perspective

Abstract: Drawing on the perceived work-family fit and balance perspective, this study investigates demands and resources as antecedents of work-life balance (WLB) across four countries (New Zealand, France, Italy and Spain), so as to provide empirical cross-national evidence. Using structural equation modelling analysis on a sample of 870 full time employees, we found that work demands, hours worked and family demands were negatively related to WLB, while job autonomy and supervisor support were positively related to W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 80 publications
13
125
0
1
Order By: Relevance
“…A sample item is: "Nowadays, I seem to enjoy every part of my life equally well". This construct has been well validated [12,25,27], including internationally [13], as well as in daily diary studies [40], showing it to be a valid and useful construct for tapping work-life balance. The measure had very good reliability in the present study (α = 0.88).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A sample item is: "Nowadays, I seem to enjoy every part of my life equally well". This construct has been well validated [12,25,27], including internationally [13], as well as in daily diary studies [40], showing it to be a valid and useful construct for tapping work-life balance. The measure had very good reliability in the present study (α = 0.88).…”
Section: Methodsmentioning
confidence: 99%
“…We controlled for factors typical of the literatures, for example [12,13,23,25,27]: [42] found that older workers were more positive about their job satisfaction. Hours Worked (1 = a minimum of 10 h/week, and then every number above that includes one to five more hours, thus 2 = 11-15 h, 3 = 16-20 h, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They conclude that mothers in Italy, Greece, and Spain are the most likely 'to mainly rely on grandparents as childcare providers ' (2012, 108). Nevertheless, another recent study conducted in Spain, Italy, France and New Zealand highlights that perceived support might not be as effective as expected for Spanish families´ work life balance (Haar et al, 2019). Family support can only provide a certain amount of balance, and as a result it is important for Governments to provide support for employees with families to ensure WLB is achieved.…”
Section: Cultural Differences In Wlc and Lwcmentioning
confidence: 97%
“…The world has gradually moved toward a so-called 24-h society [3], and some cultures (e.g., Japan) endorse long work hours, regarding it as normal for employees to work overtime [4]. However, there is evidence that extreme work hours negatively affect health and organizational performance [5], and questions have been raised about the trade-off between longer work hours and increased income on the one hand [6,7], and well-being and physical health on the other [8][9][10]. However, most previous studies focused on the effect of work hours on the organization and the individual.…”
Section: Introductionmentioning
confidence: 99%